Properties Of Latex Ferrocement In Flexure - Zulkarnain, Fahrizal; Suleiman, Mohd. Zailan (2008)
This paper discusses the durability study of polymer-modified ferrocement in comparison with conventional ferrocement particularly when exposed to severe environmental conditions.